The effect of the liver fluke Fasciola gigantica infestation on the leucocyte eosinophil cell profile on sheep - S Widjajanti; S.E Estuningsih; Subandriyo .; D Piedrafita; H.W Raadsma (Jurnal Ilmu Ternak dan Veteriner, 2004)
Eosinophil is one of the major leucocyte cell in the blood which specifically reacted on parasite infection, thus it is important to determine its profile against the F. gigantica infection. The aims of this study is to determine the differences of the eosinophil count profiles on the different breed of sheep infected with F. gigantica and its relation with the resistance of sheep bred against parasitic disease. Four groups of sheep consist of Indonesian Thin Tail (ITT) sheep, Merino sheep, backcross sheep (10 families) and F2 sheep were infected with 300 metacercariae of Fasciola gigantica. The total sheep used in this trial is 621. Those sheep were observed for 12 weeks and the blood samples were collected every 2 weeks after infection. The results showed that total eosinophil counts in all infected sheep increased after two weeks post infection and ITT sheep showed the highest counts. On the other hand, the mean fluke counts on ITT sheep is the lowest compared with the other groups of sheep. Merino and F2 sheep had the highest mean fluke counts. Three families of backcross sheep had the mean flukes count similar to ITT sheep and the other 7 families were similar to the Merino sheep. In conclusion, the highest total eosinophil count at the early stage of infection on ITT sheep might be related with the genetic resistance, which was showed by the lowest flukes count, and the resistance was inherited to some of the backcross sheep, which had similar flukes count with ITT sheep.   Key words: Fasciola gigantica, eosinophil, sheep